Analysis of the Influence of Social Media on Generation X in Choosing a North Sumatra Governor Candidate - Alberto; Octaviandy, Pieter; Tobing, Christina NM (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The dynamics of digital politics, particularly in regional head elections, are heavily influenced by the flow of information on online and social media. This study examines how online content shapes the political perspectives and preferences of Generation X within the context of the North Sumatra gubernatorial election (Pilgub Sumatera Utara), a key voter segment. Using a mixed-methods approach, this research analyzed 414 text entries from online news articles and social media comments, as well as questionnaire data from 117 Gen X respondents. Sentiment analysis revealed that online sentiment was predominantly Neutral (31.62%), followed by Negative (29.91%) and Positive (20.51%). Although Generation X actively uses social media for information (median 4.0), the direct influence of public comments was rated low (median 2.0). "Online articles," however, were found to be the most influential source (41.88%). While their trust in social media information is moderate (median 3.0), Gen X’s candidate support preference is clear (61.54%), suggesting that their choices are formed through a critical evaluation of information sources rather than passive consumption. The methodology proved effective in providing comprehensive insights into digital public opinion and the perspective of Generation X.